OPTIMASI SISTEM PERSEDIAAN PRODUK AKHIR AIR MINUM DALAM KEMASAN (AMDK) DENGAN MENGGUNAKAN KONSEP LEAN MANUFACTURING - Fitriadi, Fitriadi (Universitas Teuku Umar, 2017)
and eliminate waste. CV. Hidup Baru is a company that manufactures Bottled Drinking Water (bottled water) systems make to stock. The company set a number of production based on rough estimates of consumer demand in the previous periods. This causes the total production exceeds the amount of consumer demand for 6 periods within the range of the last 12 periods derived from historical data of the company. According to these data, too, can be seen an average of the final product inventory in the warehouse at 280% of the final product in each period. Stacking sizable inventory of this course will cause the cost of carrying cost is high. Therefore, this study aimed to optimize the amount of inventory in the warehouse by using the concept of lean manufacturing, in which the system uses the reorder point (amount of safety stock) as the minimum inventory that should be there in the shed, so companies can plan production quantities which should be generated in the next period. The results showed that with the proposed inventory system obtained total cost savings reached 716.100 cardboard carrying cost and inventory turnover value of 2 times is also larger than the current inventory system.Keywords: Lean Manufacturing, Safety Stock, Carrying Costs, Inventory Turnover